Modified CSMA/CA MAC strategy for IOT enable intra-vehicular wireless communication systems - Ali, Md Jahan (2018)
The concept of the Internet of Things (IoT) can be utilized in vehicular communication since the number of sensor nodes is raising tremendously because of the uplifting demand of different secure, safety and convenience applications. In order to do the communication among these nodes inside the vehicle, controller area network with wired architecture provides a prominent solution. However, this solution will not be viable and flexible because of the architectural complexity of wire connections in the demand of a large number of sensors inside the vehicle; hence the wired architectures are replaced by wireless ones. Moreover, scalability will be an important issue while introducing the IoT concept in Intra-Vehicular Wireless Sensor Networks (IVWSNs). The IoT enabled Intra-Vehicular Wireless Sensor Networks (IoT-IVWSNs) refer to the network where a large number of sensors are connected with each other for sharing the vehicle’s status information to develop a smart vehicular system. The number of sensor nodes in the vehicle has increased significantly due to the increasing vehicular applications. The phenomenon of congestion poses a problem in the IVWSNs where the traffic load and the number of sensors are increased. These problems can be resolved by mitigating the limitation of the existing Media Access Control (MAC) protocols. In this study firstly, it is investigated the network performance in IoT-IVWSNs with existing protocol by considering different optimized network parameters and defines the limitations. Moreover, it discusses the design of IVWSN scenario, network components, suitable wireless technology and parameters for evaluating the performance and network reliability in a scalable fashion. Secondly, a History-Based CSMA/CA MAC strategy is proposed to minimize the end to end of the network. The developed new MAC improves the network performance by reducing the limitations in the IoT-IVWSNs environment. Finally, the performance has been tested through discrete numerical simulation to show the result effectively. The results show that the network performance is increased 75% approximately in term of network performance metrics end-to-end delay.